Seismic hazard and seismicity parameters in southwestern Alborz (Nexo Revista Científica, 2021)
Alborz Province is located west of Tehran Province on the South Alborz seismic belt. Geological and seismological analyses within a radius of 200 km from the center of Karaj identified five seismic zones and seven linear seismic sources. The maximum magnitude was calculated for the seismic zones using available correlations. The Kijko and Sellevoll (1992) method was used to calculate seismicity parameters, and the graphs of the return period and the probability frequency of recurrence of the earthquake magnitude in each zone were plotted for the 475-year return period. According to the calculations, the highest and lowest earthquake magnitudes of 7.6 and 6.2 were respectively obtained in Zones 1 and 4.